An electrochemical biosensor based on a graphene oxide modified pencil graphite electrode for direct detection and discrimination of double-stranded DNA sequences. Issue 37 (1st September 2020) - Ahmadi, Mehran; Ahour, Fatemeh
Abstract : A simple electrochemical biosensor using a GO modified PGE for label-free and direct detection of ds-DNA in plasmid samples without denaturation. Abstract : The ability to directly recognize double-stranded DNA (ds-DNA) is a major challenge in disease diagnosis and gene therapy because DNA is naturally double-stranded. Herein, a novel electrochemical biosensor for the sequence-specific recognition of ds-DNA using a peptide nucleic acid (PNA) probe and graphene oxide (GO) modified pencil graphite electrode is reported and applied for the direct detection of the desired sequence in plasmid samples. For this purpose, GO was assembled onto the pencil graphite electrode surface (GO/PGE) by a simple casting method and applied for PNA probe immobilization (PNA-GO/PGE). Upon addition of ds-DNA, the interaction of the PNA probe with ds-DNA induces probe detachment from the electrode surface which results in a guanine oxidation signal decrease. Under optimized conditions, the guanine oxidation signal decreased linearly with the ds-DNA concentration increasing in the range from 30 pM to 10 nM, with a detection limit of 1.3 pM. Moreover, the proposed biosensor was applied for the sensitive and selective detection of double-stranded target DNA in plasmid samples. This proposed method could be used as a platform for direct detection of various sequences in double-stranded genomic DNA.